Analysis of Learning Writing Skills Perspective of Abdurrahman bin Ibrahim Al-Fauzan’s Theory - Nur, Tuti Laila; Nasution, Sahkholid (Universitas Yudharta Pasuruan, 2024)
Writing skills plays an important role in supporting activities in learning Arabic. This study aims to reveal the writing skills learning process for class VIII students at MTs Ali Imron and compare it with the perspective.of Prof Dr. Abdurrahman Al-Fauzan’s theory. The method used in this study is a descriptive qualitative method with the research subjects being class VIII students at MTs Ali Imron. This data collection technique uses observation and interviews. The results of this study conclude that the writing skills learning process for class VIII students at MTs Ali Imron Medan is not in accordance with the perspective of Prof, Dr. Abdurrahman Al-Fauzan’s theory. The inconsistencies are as follows; don't know how to write letters in a word and how to write vowels. Even though most of them like writing skills, teachers have not been able to provide a good learning process for the writing skills and according to the correct writing rules. So students can only just write without knowing or following the correct writing process.